A multi-criterion approach for order distribution in supply chain management. (16th April 2009) - Chung, S.H.; Lau, H.C.W.; Chan, F.T.S.
This paper developed a multi-criteria Genetic Algorithm (GA), specifically designed for solving distribution problems in supply chain management. The proposed algorithm is discussed with an order distribution problem in a demand-driven supply chain network. The proposed methodology combines Analytic Hierarchy Process with GAs. The numerical results comparison obtained from the new approach shows that it is reliable and robust.